Analisa Gaya Pembuatan Keputusan Pentadbir Sekolah - Wan Yasima, Mohamad Amin (1998)
This research aims to identify the style of decision-making of a school administrator, types of decision, style of decision-making being practice as well as teachers‘ involvement in decision-making. This case study involves two school namely Sekolah Menengah Sultan Abdul Halim and Sekolah Menengah Jitra. Based on the teachers’ perception, the data shows that primary style of decision making implemented by an administrator is Y 1 Style , followed by A2 Style , Y2 Style and Al Style . Apart from that, based on the teachers’ perception too, Al Style is mainly practiced by administrator in curriculum administration, co-curriculum administration assistance service, human resourse, curriculum changes and special programmers, while A2 Style is used by administrator for administration assistance service for students and serious discipline problems. In terms of style of involvement, it is discovered that the percentage of intellect involvement is higher than reaction involvement. Pearson Correlation Matrics Items analysis reveals that A2 decision-making style is significantly related to Y1 and Y2 styles, whereby, Y1 and Y2 styles are significantly related too.